α(2)-Adrenoceptor Functionality in Postmortem Frontal Cortex of Depressed Suicide Victims - Valdizán, Elsa M. (2010)
BACKGROUND: Alterations in brain density and signaling associated with monoamine receptors are believed to play a role in depressive disorders. This study evaluates the functional status of α(2A)-adrenoceptors in postmortem frontal cortex of depressed subjects. METHODS: G-protein activation and inhibition of adenylyl cyclase (AC) activity induced by the α(2)-adrenoceptor agonist UK14304 were measured in triplicate in samples from 15 suicide victims with an antemortem diagnosis of major depression and 15 matched control subjects. RESULTS: Basal [(35)S] guanosine γ thio-phosphate (GTPγS) binding and cyclic adenosine monophosphate accumulation did not differ between groups. In depressed victims, an increase in [(35)S] GTPγS binding potency (EC(50) = .58 μmol/L vs. EC(50) = 3.31 μmol/L; p < .01; depressed vs. control) and a significant reduction in the maximal inhibition of AC activity (I(max) = 27 ± 4% vs. I(max) = 47 ± 5%; p < .01) were observed after incubation with the α(2)-adrenoceptor agonist UK14304. No differences were found between antidepressant-free and antidepressant-treated subjects. A significant relationship between EC(50) values for [(35)S] GTPγS and I(max) values for AC assay was found (n = 30; r = −.43; p < .05). CONCLUSIONS: The dual regulation of α(2A)-adrenoceptor signaling pathways raises the possibility that factors affecting the G-protein cycle and/or selective access of Gα(i/o)–protein to AC might be relevant to receptor abnormalities in depression, providing further support for the involvement of α(2A)-adrenoceptors in the pathogenesis of depression.